Carcass profile and chemical characteristic of male Kacang goat (Capra aegragus hircus) - I, Mirdhayati; J, Hermanianto; CH, Wijaya; D, Sajuthi (Indonesian Animal Sciences Society, 2014)
The purpose of this research was to characterize the carcass profile and chemical characteristic of male Kacang goat (local name for Capra aegragus hircus) from two different slaughter ages, namely < 1.5 and > 1.5 years old. Kacang goats generally is slaughtered for consumption at these ages. The body part used for chemical analysis was the carcass leg. Data was analyzed statistically by t test. Results showed that there was no profile differences of the carcass from both group ages obtained from similar rearing system and at common range of body weight for slaughtering. Chemical characteristics measured by the contents of protein, fat, moisture, ash and cholesterol level in goat meat showed no differences between the two slaughter ages. Dominant amino acids found in the goat meat was glutamic acid, aspartic acid, leucyne and lysine. Saturated and unsaturated fatty acid profiles in the goat meat did not show any different between the two slaughter ages, except for eicosatrienoic acid, in which the meat from the younger goat had significantly higher content of eicosatrienoic acid. The meat of male Kacang goat of both groups is a potential source of healthy meat, based on its low fat content, functional amino acid composition, higher desirable fatty acids and fatty acid ratio of omega 6 : omega 3 which corresponds to the values recommended by American Heart Association 2008. Key Words: Male Kacang Goat (Capra aegragus hircus), Carcass, Cholesterol, Amino Acids, Fatty Acids